2013
DOI: 10.1111/mec.12524
|View full text |Cite
|
Sign up to set email alerts
|

On the accumulation of deleterious mutations during range expansions

Abstract: We investigate the effect of spatial range expansions on the evolution of fitness when beneficial and deleterious mutations cosegregate. We perform individual-based simulations of 1D and 2D range expansions and complement them with analytical approximations for the evolution of mean fitness at the edge of the expansion. We find that deleterious mutations accumulate steadily on the wave front during range expansions, thus creating an expansion load. Reduced fitness due to the expansion load is not restricted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
495
2
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(537 citation statements)
references
References 83 publications
(197 reference statements)
39
495
2
1
Order By: Relevance
“…Some studies showed similar numbers of putatively deleterious alleles per individual across human populations (3,4). In contrast, other recent studies reported a significant increase in the number of deleterious alleles (5, 37) and a higher additive genetic load in non-African populations compared with African populations (5,6,8,37,38). Our present findings of a higher genetic load in dogs compared with wolves supports the view that recent demographic history can affect genetic load.…”
Section: Significancecontrasting
confidence: 53%
See 1 more Smart Citation
“…Some studies showed similar numbers of putatively deleterious alleles per individual across human populations (3,4). In contrast, other recent studies reported a significant increase in the number of deleterious alleles (5, 37) and a higher additive genetic load in non-African populations compared with African populations (5,6,8,37,38). Our present findings of a higher genetic load in dogs compared with wolves supports the view that recent demographic history can affect genetic load.…”
Section: Significancecontrasting
confidence: 53%
“…Consequently, understanding the reasons why deleterious mutations persist in populations and the role of demographic history in this process is of considerable interest (1)(2)(3)(4)(5)(6)(7)(8)(9). The radiation of domestic dogs offers a unique opportunity to address these questions.…”
mentioning
confidence: 99%
“…Given sufficient time, then, an optimal strategy on the invasion front would be to reallocate resources from competitive ability and towards dispersal [3]. How often, and indeed whether, this optimal strategy emerges on invasion fronts (where stochastic forces often lead to nonoptimal phenotypes dominating: [24][25][26]) is yet to be clarified with empirical studies. In our simulations, the effectiveness of a landscape barrier was very sensitive to the degree of long-distance dispersal.…”
Section: Discussionmentioning
confidence: 99%
“…B 283: 20153037 [35,36], enhanced kin competition [37], spatial sorting [38] and enhanced spatial selection [39] come into play. Mutation surfing can undermine fitness directly [24][25][26], while spatial sorting, enhanced spatial selection and kin competition work to fashion a phenotype that is adept at rapid dispersal, even if that dispersal enforces compromises in traits that enhance fitness in equilibrium populations [3]. By translocating range core individuals to the range edge, we eliminate the evolutionary conditions of the invasion front (the density gradient that drives spatial sorting as well as the high relatedness driving kin-competition effects), and bring invasion front phenotypes into direct conflict with fitter range core phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, there has long been interest in using spatial models for understanding processes underlying geographical variation in genetic polymorphisms (Wright, 1946;Kimura and Weiss, 1964). Spatial genetic models that investigate spatial and temporal dynamics remain an active area of research in population genetics (see for example Pieschl et al, 2013) and are becoming increasingly useful with the widespread availability of genome-scale data and computational power to generate more complex and realistic models that better reflect biological reality (Gompert et al, 2014).…”
Section: Introductionmentioning
confidence: 99%